Sewability of Pina fabric - Pagcu, Grace Cielo R.
Sewability of Pina as an experimental research was undertaken by the researcher to provide valuable sewing information on handling pina fabric. This research was for the benefit of current and future pina fabric users; the garment manufacturers, fashion designers, and sewers. To determine the sewability of pina fabric; tests were conducted using two different sewing brands, fabric and sewing variables of varying needle size, stitches per inch (spi), sewing thread, direction of sewing and type of sewing machine. For the sewing thread, the breaking strength, twist and yarn count were obtained. For the fabric samples; breaking strength, twist and yarn count and weight were obtained. Sewability of Pina had been attained by identifying the best sewing variables: (1) spi: either 10 or 12; (2)Needle size: 9;(3) Thread brand: Astra; (4) Type of Sewing Machine: Manual (5)Directional Sewing: Care in sewing the curved directions.